Pertumbuhan dan Produksi Japanese Mint (Mentha arvensis L.) pada Berbagai Komposisi Media Tanam untuk Mendukung Pengembangan Minuman Fungsional Cucumint - Sekar Sari; Siwitri Munambar; R R Siti Astuti (PAKIS JOURNAL INSTITUTE, 2026)
Mentha arvensis L., commonly known as Japanese mint, is an aromatic plant with potential as a primary raw material for the functional beverage Cucumint. The availability of high-quality raw materials strongly depends on successful cultivation, including the use of appropriate growing media. This study aimed to examine the effects of various growing media formulations on the growth and yield of Japanese mint as a raw material for Cucumint functional beverage. The study was conducted from November 2025 to June 2026 at the Teaching Factory (TEFA) Garden, Sempu, Sleman, Special Region of Yogyakarta. A one-factor randomized complete block design (RCBD) was used, consisting of four growing media treatments: P1 (soil + solid organic fertilizer derived from rabbit manure), P2 (soil + solid organic fertilizer derived from rabbit manure + cocopeat), P3 (soil + solid organic fertilizer derived from rabbit manure + rice husk charcoal), and P4 (soil + solid organic fertilizer derived from rabbit manure + leaf compost). Each treatment was replicated six times. The observed variables included plant height, number of branches, number of leaves, and fresh leaf weight. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level. The results showed that growing media formulation significantly affected all observed variables. Treatment P3 produced the best results, with a plant height of 26.617 cm, 10.39 branches, 84.83 leaves, and a fresh leaf weight of 5.983 g at 35 days after planting (DAP). Therefore, the growing medium consisting of soil, solid organic fertilizer derived from rabbit manure, and rice husk charcoal at a ratio of 1:1:1 was the most promising formulation for improving the growth and yield of Japanese mint as a raw material for Cucumint functional beverage.